Supernova 1987A : envelope metallicity and the nature of the soft X-ray component. - Mastichiadis, A.; Kylafis, N.; Ventura, J. (Astronomy and Astrophysics, 1989)
The observed X-ray spectra reported by the GINGA and MIR-HEXE satellite experiments contain information on the metallicity of the Supernova's expanding envelope. Using a Monte Carlo code to simulate the Compton degradation of the ^56^Co -produced γ-rays, we calculate the emerging X-ray spectrum for various metallicities. The observed spectra are compatible with a low (less than solar) metal abundance, while an additional soft component, independent of the ^56^Co source is probably required in order to account for the data. The evolution of the spectral hardness is used as a sensitive indicator of the nature of the soft component, and of the possible contribution of an imbedded pulsar to the X-ray spectrum.
Keywords: Astrophysics; Cobalt Isotopes; Metallicity; Monte Carlo method; Neutron stars; Stellar Envelopes; Supernova 1987a; X Ray Sources; X Ray Spectra